A Analisis Kemampuan Literasi Sains dan Berpikir Kritis Siswa SMP pada Pembelajaran IPA: Analisis Kemampuan Literasi Sains dan Berpikir Kritis Siswa SMP pada Pembelajaran IPA - Cahyani, Dwi Kurnia; Nugroho, Ary Susatyo; Nizaruddin; Hayat, Muhammad Syaipul (UNIB Press, 2024)
Students' scientific literacy and critical thinking skills are very important to meet the challenges of the 21st century, especially in science learning. This research aimed to determine the scientific literacy and critical thinking abilities of junior high school students. This research uses quantitative descriptive methods. Data collection techniques were done using instruments to test students' scientific literacy and critical thinking abilities. The research subjects were 29 class VIII students. The results of the research show that the students' scientific literacy abilities with an average score of (29.89) are very poor. Of the three indicators of scientific literacy based on PISA, evaluating and designing scientific research received a score of (41.38) poor, interpreting scientific data and evidence received a score of (20.69) very poor and explaining phenomena scientifically (27.59) very poor. Meanwhile, critical thinking skills received an average score of (37.93) which was very poor. Of the five indicators of critical thinking based on the Ennis framework, giving a simple explanation got a score of (79.31) good, building a basic classification got a score of (24.14) very poor, making an inference got a score of (31.03) very poor, making an explanation more continued to get a score of (13.79) which was very poor, managing strategies and tactics got a score of (37.93) which was very poor. The results of this research showed that the scientific literacy and critical thinking abilities of junior high school students in science learning were still low.